Ontology Application to Construct Inductive Modeling Tools with Intelligent Interface - Pidnebesna, H.A.; Pavlov, A.V.; Stepashko, V.S. (Control systems & computers, 2020)
This paper is devoted to the analysis of sources in the field of development and building intelligent user interfaces. Particular attention is paid to presenting an ontology-based approach to constructing the architecture of the interface, the tasks arising during the development, and ways for solving them. An example of construction of the intelligent user interface is given for software tools of inductive modeling based on the detailed analysis of knowledge structures in this domain.